Efficient in vitro organogenesis and plantlets regeneration in sesame (Sesamum indicum L.)-an important oilseed crop - T. Deenathayalan, R. Anandan, K.V. Deepak; S. Murugan, M. Prakash, M. Vignesh, B. Priyadharshini (Horticultural Biotechnology Research)
The regeneration methods in Sesame (Sesamum indicum L.) already developed were genotype dependent and were unsuccessful for Indian cultivars. Hence, an efficient protocol for in vitro organogenesis and plant regeneration in sesame was attempted with TMV 3 cultivar. Immature cotyledons derived from 1-week old seedlings were cultured on MS (Murashige and Shoog) medium fortified with different concentrations of 6-benzylaminopurine (BAP), thidiazuran (TDZ) and kinetin for adventitious shoot induction. It was found that optimal medium for direct shoot formation was MS with BAP (2.0 mg/l) at a frequency of 74% with an average of 4.5 shoots per expalnt. The shoot regeneration frequency was significantly reduced with either TDZ or kinetin when compared with BAP alone. Elongated individual shoots were transferred on MS media supplemented with Indole Butyric Acid (IBA; 0.5 mg/l) showed rooting frequency of 70%. The rooted plantlets were acclimatized to potting mixture containing sand, soil and clay mixture and grown to maturity with survival rate of 65 %. No phenotypic aberrations were observed among the ex vitro transferred plantlets. The protocol described here assures a high frequency of shoot regeneration, root induction and also plant survival rate.